Study on the Rossby Waves Parameters in Total Ozone Over the Arctic in 2000–2021 - Zhang, Chenning; Grytsai , Asen; Evtushevsky, Oleksandr; Milinevsky, Gennadi; Andrienko, Yulia; Shulga, Valerii; Klekociuk , Andrew; Rapoport, Yuriy; Han , Wei (Research Advances in Environment, Geography and Earth Science Vol. 3, 2024)
The breaking of Rossby waves in the polar stratosphere results in rapid increases in temperature, known as sudden stratospheric warmings. The purpose of this work is to study Rossby wave parameters in total ozone over the Arctic in 2000–2021. We consider the averages in the January–March period, when stratospheric trace gases (including ozone) in sudden stratospheric warming events are strongly disturbed by the planetary waves. To characterize the wave parameters, we analyzed ozone data at the latitudes of 50° N (the sub-vortex area), 60° N (the polar vortex edge) and 70° N (inner region of the polar vortex). Total ozone column (TOC) measurements over 22-year time interval were used from Total Ozone Mapping Spectrometer / Earth Probe and Ozone Mapping Instrument / Aura satellite observations. The TOC zonal distribution and variations in the Fourier spectral components with zonal wave numbers m = 1–5 are presented. The daily and interannual variations in TOC, amplitudes and phases of the spectral wave components, as well as linear trends in the amplitudes of the dominant quasi-stationary wave 1 (QSW1) are discussed. The positive TOC peaks inside the vortex in 2010 and 2018 alternate with negative ones in 2011 and 2020. The extremely low TOC at 70° N in 2020 corresponds to severe depletion of stratospheric ozone over the Arctic in the strong vortex conditions due to anomalously low planetary wave activity and a high positive phase of the Arctic Oscillation. The Arctic Oscillation, as one of the key factors of climate variability in the Northern Hemisphere, negatively correlates with TOC at the 95% confidence level (r = -0.40 \(±\) 0.36 and r = -0.56 \(±\) 0.29 at 50° N and 70° N, respectively). Interannual TOC variations in the sub-vortex region at 50° N are accompanied by a negative trend of –4.8 Dobson Units per decade in the QSW1 amplitude, statistically significant at 90% confidence level, while the trend is statistically insignificant in the vortex edge region and inside the vortex due to the increased variability in TOC and QSW1. The processes associated with quasi-circumpolar migration and quasi-stationary oscillation of the wave-1 phase depending on the polar vortex strength in 2020 and 2021 are discussed.